2015
DOI: 10.1186/s12929-015-0191-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of severe dengue disease – a review

Abstract: Dengue virus infection presents a wide spectrum of manifestations including asymptomatic condition, dengue fever (DF), or severe forms, such as dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS) in affected individuals. The early prediction of severe dengue in patients without any warning signs who may later develop severe DHF is very important to choose appropriate intensive supportive therapy since available vaccines for immunization are yet to be approved. Severe dengue responses include T and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 78 publications
4
72
0
5
Order By: Relevance
“…Indeed, most dengue cases from studies performed in other parts of the world (42) and our Indian cohort had some IFN-γ in the plasma (28). This suggests that, perhaps, these cells and/or other immune cells were making IFN-γ in vivo prior to the arrival of the patient at the clinic, but a vast majority of them may have lost the in vitro IFN-γ production capacity by the time the patient experienced clinical symptoms and presented to the clinic.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, most dengue cases from studies performed in other parts of the world (42) and our Indian cohort had some IFN-γ in the plasma (28). This suggests that, perhaps, these cells and/or other immune cells were making IFN-γ in vivo prior to the arrival of the patient at the clinic, but a vast majority of them may have lost the in vitro IFN-γ production capacity by the time the patient experienced clinical symptoms and presented to the clinic.…”
Section: Discussionmentioning
confidence: 90%
“…Activation of 'T' cells results in release of inflammatory cytokines triggering death of cells through apoptosis which contributes to severe dengue. 16 Neutrophilia was noted in 11% of cases and a normal differential in 24%. However, few studies showed a higher proportion of cases with neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, preexisting antibodies acting on bone marrow progenitor cells could facilitate entry, replication, and spread of DENV by a process known as antibody-dependent enhancement have been reported [13]. Infected phagocytic cells may activate other effector mechanisms to produce vasoactive cytokines that cause endothelial cell damage resulting in transient plasma leakage in DHF [6]. Alternatively, activated phagocytic cells can produce proinflammatory cytokines by the CLEC5A-mediated signaling to induce DHF [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many hypotheses have been implicated, including antibody-mediated enhancement on viral entry and replication in Fc-bearing phagocytic cells [3], individual genetic background [4], viral strain differences [5], a cascade of cytokine storm resulting from viral infection in immune cells [6], and hematological disorders [7,8]. …”
Section: Introductionmentioning
confidence: 99%